Socio-Economic Determinants of Consumer Demand for Non- Timber Forest Products in Ogun and Osun States, Southwest Nigeria (2013)
There is a dearth of research effort on the individual and household characteristics that affect the consumption of _on-Timber Forest Products (_TFPs) in parts of Southwest _igeria. Yet, understanding the factors driving demand for _TFPs is crucial for managing supplies sustainably. Therefore, this study examined the socio-economic determinants of consumer demand for _TFPs in Ogun and Osun States, Southwest _igeria. A survey involving 320 respondents randomly selected from eight communities in each of Ijebu East Local Government Area (LGA) of Ogun State and Ife South Local Government Area (LGA) of Osun State was carried out using questionnaires. Data were collected on five top priority species including: bush mango (Irvingia gabonensis), African walnut (Plukenetia conophora), chewingstick (Massularia acuminata), fever-bark (Annickia chlorantha syn. Enantia chlorantha) and bush pepper (Piper guineense). Both descriptive and inferential statistics involving frequency tables, percentages, Likert scale, chi-square and multiple linear regression were used in analyzing the data at P = 0.05. Respondents’ sex, age, marital status, educational attainment and primary occupation had significant impacts on the level of consumption of P. conophora and A. chlorantha, while that of M. acuminata was significantly impacted by both marital status and household size. Primary occupation and age of respondents also significantly impacted the level of consumption of P. guineense, whereas only household size had a significant impact on the level of consumption of I. gabonensis. Products’ price, taste and substitute had no significant effect on _TFPs consumption. Although, each of the _TFPs has different socio-economic demand and niche among the consumers, the most determining factors of consumption were product availability and season of the year. The results of this study are valuable for predicting _TFPs consumption pattern and for policy orientation that targets sustainable use of the products